Optimal planning and operation strategies of a battery swapping station in an electric vehicle corridor - Xie, Zhaoqing (Nanyang Technological University, 2025)
Electric vehicles (EVs) present a promising solution to mitigate emissions from the transportation system, while battery swapping technology is proven to be an EV refuelling mode that acquires a much shorter recharge time compared with plug-in charging. This thesis addresses the morning commuter problem within an EV corridor equipped with a battery swapping station. EV travellers are categorized by their travel mode: driving through the corridor, driving with one-time battery swapping, and taking the transit line. We model this scenario using a Y-shaped bottleneck congestion framework, treating the swapping station as an upstream bottleneck. This study identifies how bottleneck capacity and demand ratios influence the commuter travel patterns at departure time equilibrium, classifying these patterns into two main scenarios and five subcases, each with corresponding commuter cost functions. Using these cost functions, we develop two optimization models aimed at 1) determining the optimal service prices of battery swapping operations and 2) jointly optimizing the capacity and service price of the battery swapping station. Numerical experiments validate the proposed operation pricing and investment strategies, ensuring the optimal performance and profitability of the battery swapping station.